ELECTRONIC HUMAN RESOURCES MANAGEMENT PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND CONTINUANCE USAGE INTENTION: THE MEDIATING ROLE OF USER SATISFACTION IN JORDANIAN HOTELS SECTOR - Adnan M. Rawashdeh (International Journal for Quality Research, 2021)
This paper intends to evaluate the relationship of Electronic Human Resources Management )e-HRM)' Perceived Usefulness (PU), e-HRM Perceived Ease of Use (PEOU), and Continuance Usage Intention (CUI) in the context of the Jordanian Hotel Sector (JHS), and identify the mediating role of user satisfaction towards e-HRM between e-HRM PEOU, PU, and CUI evident in non-Western contexts and specifically in the Middle East region. An empirical study was carried out in JHS, data were collected from (123) HR professionals are working in 30 Five Stars hotels as a high ranked hotel in Jordan. The primary data collection followed a structured questionnaire. It examined using the 'Structural Equation Modeling' (SEM) methodology to test the relationship and effects among the variables, and for analysis, SPSS and Smart-PLS were applied. from the SEM analysis, it is evident that the measurement model that has been proposed and structural model is a satisfaction of the necessary fitness conditions, it revealed that e-HRM PEOU was positively related to CUI, while, e-HRM PU showed no significant effect on CUI, user satisfaction showed a direct and positive influence on CUI. As for the indirect impact, e-HRM PU had no immediate impact on CUI and no indirect effect on CUI through user satisfaction e-HRM PEOU was positively related to user satisfaction, which, in turn, was positively related to CUI. Thus user satisfaction was shown to play a mediating role between e-HRM PEOU and e-HRM CUI. The paper has implications for providing insights for the e-HRM user to manage the usage of e-HRM efficiently. In general, enhancing user satisfaction toward e-HRM can result in a high level of CUI. Besides, users should realize PU and user satisfaction to improve the usage of e-HRM and CUI.